Perencanaan Jadwal Produksi Induk pada Produksi Sweater dengan Pendekatan Time Fences - Anshor Muhamad Sujadi; Nita P.A Hidayat (Jurnal Riset Teknik Industri, 2023)
Abstract. Indah Fashion is a home industry engaged in fashion in the form of sweater clothes made from knitted yarn in Indonesia. The strategy respond to the market in Indah Fashion is Make to Stock (MTS) and Make to Order (MTO). Currently, Indah Fashion is faced with the problem of lack of stock available in stores and delays in fulfilling orders for MTO. This happens due to the absence of a production schedule and always receiving orders from consumers regardless of available capacity. Therefore, the master production schedule planning method using Time Fences is used as an effort to organize and control production schedules for MTS and MTO strategies. This research was conducted to compile a production schedule by applying the Time Fences method. The stages carried out in this study are predicting demand, planning production, and forming production schedules using the Time Fences method. The establishment of a production schedule using the Time Fences method begins by identifying the arrival of additional orders with three Time Fences zones. After that, Time Fences are scheduled by generating the Project Available Balance (PAB) value. The results obtained using the Time Fences method on the 2022 order data have positive PAB values and exceed safety stock for several periods. The PAB value indicates that it needs to be re-scheduled. Re-schedule is done without changing the actual order production schedule. Therefore, for additional orders will be placed after the actual order scheduling is completed. The result of rescheduling in a certain period result in sweater products requiring more time than RT + OT capacity to complete additional orders. Abstrak. Indah Fashion merupakan home industry yang bergerak pada bidang fashion berupa pakaian sweater berbahan benang rajut di Indonesia. Strategi merespon pasar yang diterapkan oleh Indah Fashion yaitu Make to Stock (MTS) dan Make to Order (MTO). Saat ini Indah Fashion dihadapkan dengan permasalahan kekurangan stock yang tersedia di toko dan keterlambatan pemenuhan pesanan untuk MTO. Hal itu terjadi akibat tidak adanya jadwal produksi dan selalu menerima pesanan dari konsumen tanpa melihat kapasitas tersedia. Oleh karena itu, metode perencanaan jadwal produksi induk dengan menggunakan Time Fences digunakan sebagai upaya mengatur dan mengontrol jadwal produksi untuk strategi MTS dan MTO. Penelitian ini dilakukan untuk menyusun jadwal produksi dengan menerapkan metode Time Fences. Tahapan yang dilakukan dalam penelitian ini yaitu melakukan prediksi permintaan, perencanaan produksi dan pembentukan jadwal produksi menggunakan metode Time Fences. Pembentukan jadwal produksi menggunakan metode Time Fences diawali dengan mengidentifikasi kedatangan pesanan tambahan dengan tiga zona Time Fences. Setelah itu dilakukan penjadwalan Time Fences dengan menghasilkan nilai Project Available Balance (PAB). Hasil yang diperoleh menggunakan metode Time Fences pada data order Tahun 2022 memiliki nilai PAB positif dan melebihi safetystock untuk beberapa periode. Nilai PAB tersebut menunjukan bahwa perlu dilakukan re-schedule. Re-schedule dilakukan tanpa mengubah jadwal produksi pesanan aktual. Oleh karena itu untuk pesanan tambahan akan dilakukan setelah penjadwalan pesanan aktual selesai. Hasil penjadwalan re-schedule pada periode tertentu mengakibatkan produk sweater membutuhkan waktu yang lebih dari kapasitas RT+OT untuk menyelesaikan pesanan tambahan.